2023
DOI: 10.3390/ijerph20021566
|View full text |Cite
|
Sign up to set email alerts
|

Hope-Based Program for Portuguese Outpatients with Advanced Chronic Illness in a Community Setting: A Randomized Control Trial

Abstract: Background: Hope is widely considered a subjective phenomenon able to bring beneficial consequences to human health and existence. Maintaining hope amid a life-threatening disease and during palliative care is critical. The study aims to examine the effectiveness of a psychosocial supportive Hope Promotion Program (HPP) in enhancing hope, comfort, and quality of life in Portuguese adult outpatients with advanced and progressive chronic illness. Method: Using a parallel Randomized Control Trial (RCT) with pre-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Increasing hope levels can satisfy and empower patients, enhancing their resilience against the disease. 31 However, a saturation point at a hope level of approximately 36 was observed, beyond which no additional reduction in FCR risk occurs. This indicates that in the context of low social support, merely increasing hope is insufficient.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Increasing hope levels can satisfy and empower patients, enhancing their resilience against the disease. 31 However, a saturation point at a hope level of approximately 36 was observed, beyond which no additional reduction in FCR risk occurs. This indicates that in the context of low social support, merely increasing hope is insufficient.…”
Section: Discussionmentioning
confidence: 97%
“…In patients with lower social support, the study revealed a significant nonlinear relationship between hope levels and FCR. Increasing hope levels can satisfy and empower patients, enhancing their resilience against the disease 31 . However, a saturation point at a hope level of approximately 36 was observed, beyond which no additional reduction in FCR risk occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Several models of using narrative in supporting terminally ill patients and their families exist, including dignity therapy, Short-Term Life Review, meaning-making intervention, and the Living with Hope Program. [7][8][9][10][11] Dignity therapy asks patients to reflect on the value of their life and relationships with a trained health care professional. Sessions last between 30 and 60 minutes, and patients' stories are transcribed into a written account for families.…”
Section: "Smentioning
confidence: 99%
“…Services that combine life review work with this legacy component are increasingly recognized by facilitators and patients as valuable work 6 . Several models of using narrative in supporting terminally ill patients and their families exist, including dignity therapy, Short-Term Life Review, meaning-making intervention, and the Living with Hope Program 7-11 . Dignity therapy asks patients to reflect on the value of their life and relationships with a trained health care professional.…”
mentioning
confidence: 99%